Analisis Dampak Pembelajaran Matematika dalam Kemampuan Kognitif dan Keterampilan Hidup Siswa Sekolah Dasar - Astri Resti Rahmadani (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
This research was conducted to find out the impact of mathematics learning on the cognitive abilities and life skills of elementary school students. This research uses a questionnaire to find out how they have learned mathematics. This research uses a qualitative approach by utilizing a questionnaire as an instrument. The distribution contained 15 questionnaire statements given to 18 class VI students. The results of the analysis show that most mathematics learning has a positive impact on students' cognitive and life skills. Through mathematics lessons, students can hone their ability to think critically, systematically, so that they can solve problems from the questions they are given and problems found in everyday life. Although there are still many who do not feel the benefits of mathematics itself.